Mini-open double row gluteus medius repair provides good short-term functional outcomes. Issue 3 (21st October 2019) - DeFroda, Steven; Silverman, Ariel; Quinn, Matthew; Tabaddor, Ramin
Abstract: Gluteus medius (GM) tears are recognized as a significant cause of lateral hip pain. While non-operative management can be effective, those who fail this treatment modality may be indicated for operative intervention. There is no widely agreed upon 'gold standard' technique with regards to open, mini-open and endoscopic repair. Our study prospectively enrolled 31 patients undergoing the authors preferred 'mini-open' repair technique with patients completing pre- and post-operative patient reported outcome measures (PROMs) in the form of the Modified Harris Hip Score, Visual Analogue pain Scale, Hip Outcomes Score for Activities of Daily Living and Hip Outcomes Score for Sports-Related Activities (HOS-SSS). The effect of anxiety/depression on outcomes was also examined. Patients had an average follow-up of 6 months. There was a statistically significant increase in all PROMs in the 31 patients undergoing mini-open repair. A sub-group of patients with self-reported history of anxiety/depression via patient intake paperwork experienced less improvement than those without, however this cohort still had significant improvement in all categories except HOS-SSS. Our study shows that a mini-open GM repair technique provides good patient reported outcomes at 6 months, and allows for improved cosmesis compared with traditional open techniques utilizing a larger surgical incision. It is important to counsel patients with a history of anxiety/depression that while they can expect significant functional improvement, that their improvement may be less than patients without these comorbidities.